2011
DOI: 10.1128/aem.05925-11
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Based Metagenomic Screening and Biochemical Characterization of Bovine Ruminal Protozoan Glycoside Hydrolases

Abstract: The rumen, the foregut of herbivorous ruminant animals such as cattle, functions as a bioreactor to process complex plant material. Among the numerous and diverse microbes involved in ruminal digestion are the ruminal protozoans, which are single-celled, ciliated eukaryotic organisms. An activity-based screen was executed to identify genes encoding fibrolytic enzymes present in the metatranscriptome of a bovine ruminal protozoan-enriched cDNA expression library. Of the four novel genes identified, two were cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(27 citation statements)
references
References 56 publications
4
19
0
4
Order By: Relevance
“…Rumen anaerobic fungi and protozoa are capable of efficient hydrolysis of cellulose, as demonstrated by biochemical assays of their cellulase activities (60)(61)(62). We show that enzymes of the GH5, GH9, and GH48 families are the predominant cel-GHs from rumen anaerobic fungi and protozoa, as reported previously (22).…”
Section: Discussionsupporting
confidence: 60%
“…Rumen anaerobic fungi and protozoa are capable of efficient hydrolysis of cellulose, as demonstrated by biochemical assays of their cellulase activities (60)(61)(62). We show that enzymes of the GH5, GH9, and GH48 families are the predominant cel-GHs from rumen anaerobic fungi and protozoa, as reported previously (22).…”
Section: Discussionsupporting
confidence: 60%
“…Additionally, a lower carboxymethyl cellulose activity in the rumen of defaunated lambs was observed, showing lower cellulose digestibility than those faunated (Santra and Karim 2002). Additionally, studies of metagenomic screening of glucosidases and metatranscriptomes have shown that a diverse range of glycoside hydrolases are present in the rumen ciliates (Findley et al 2011;Qi et al 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Limited information exists on the role of rumen protozoa in fiber degradation 24, 25 , but functional protozoal glycosyl hydrolases have been identified, successfully expressed and biochemically characterized 26 . Rumen fiber degradation depends on complex interactions between bacteria, protozoa and fungi and the plant cell wall.…”
Section: Discussionmentioning
confidence: 99%